2020
DOI: 10.5007/2175-8042.2020e72330
|View full text |Cite
|
Sign up to set email alerts
|

Imagem corporal masculina: revisão integrativa da produção científica latino-americana (2005-2019)

Abstract: Esse estudo tem como objetivo realizar uma revisão integrativa da literatura científica latino-americana, dos últimos 15 anos, acerca dos aspectos socioculturais que perpassam a imagem corporal masculina. Na perspectiva das pesquisas de Revisão Integrativa, foram analisados 115 artigos, disponíveis nas bases virtuais Lilacs, SciELO e PePsic, publicados no período entre 2005 a 2019. O conjunto de estudos analisados revela a centralidade dos aspectos socioculturais na construção da imagem corporal masculina e no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…In a systematic review of the process of social construction of masculinities (Martins & Nascimento, 2020) it is observed that only cisgender men were considered, which suggests that transgender men tend to be excluded. It is necessary to adjust the focus of attention to this segment of the LGBTQIA+ population in order to understand their specificities and have a broader look at masculinities, incorporating divergent and non-hegemonic perspectives.…”
mentioning
confidence: 99%
“…In a systematic review of the process of social construction of masculinities (Martins & Nascimento, 2020) it is observed that only cisgender men were considered, which suggests that transgender men tend to be excluded. It is necessary to adjust the focus of attention to this segment of the LGBTQIA+ population in order to understand their specificities and have a broader look at masculinities, incorporating divergent and non-hegemonic perspectives.…”
mentioning
confidence: 99%